ANALISIS FAKTOR INTERNAL DAN EKSTERNAL YANG MEMENGARUHI TINGKAT KECEMASAN Kajian pada mahasiswa Program Studi Pendidikan Profesi Dokter Program Profesi pada stase mayor di RSUD Ulin Banjarmasin periode Oktober tahun 2022 - Chaerany, Annisa Fitria; Fitria, Yanti; Triawanti, Triawanti; Fadhilah, Syaiful; Audhah, Nelly Al (Homeostasis, 2023)
Anxiety is an individual psychological condition that arises when stress occurs, characterized by feelings of tension, fear, worry, and is accompanied by a physical response in the form of a fast heart beating, hypertension, and so on. Medical students tend to have a higher level of anxiety sompared to other student. The clinical student anxiety factors themselves are classified into 2 namely internal factors which include gender, age, and external factors which include environment, workload, and experience. This study aims to analyze internal and external factors that trigger student anxiety. This research is an analytic observational study with a cross-sectional approach. The result of this study indicates that the level of student anxiety includes the not anxiety category of 57 people (36,3%), mild anxiety in 64 people (40,7%), moderate anxiety in 26 people (16,5%), severe anxiety in 10 people (6,5%) and no students with very severe anxiety were found. The Chi-Square test showed that there was an effect of gender p= 0,000, residence p=0,006, the level in station p=0,000, and the previous station p=0,000 on the level of anxiety, while there was no effect of the length of anxiety on the p value=0,323.  It can be concluded that there are internal and external factors that influence the level of student anxiety, namely gender, place of residence, the level at the station, and the previous station